Long-term outcome in Wiskott-Aldrich syndrome and X-linked thrombocytopenia patients: an observational -prospective multi-center study of the Italian Primary Immune Deficiency Network (IPINET) - Soresina, Annarosa; Rondelli, Roberto; Notarangelo, Lucia Dora; Locatelli, Franco; Aiuti, Alessandro; Biffi, Alessandra; Rabusin, Marco; Pignata, Claudio; Menna, Giuseppe; Prete, Arcangelo; Faraci, Maura; Rovelli, Attilio; et al. (EClinicalMedicine, 2025)
Wiskott-Aldrich Syndrome (WAS) is characterized by eczema, infections, and severe bleeding, but may also include autoimmunity and malignancy. Subjects with X-linked thrombocytopenia (XLT) can display a mild phenotype, although severe complications may occur at any age. WAS and XLT are caused by mutations of the WAS gene. However, retrospective studies have shown conflicting results about their genotype–phenotype correlation and their relative risk of complications. To evaluate the outcome of patients with WAS or XLT, since January 2004, patients with identified WAS mutations were enrolled in the WAS/XLT IPINet registry at diagnosis and annually evaluated until December 2018 by participating AIEOP-IPINet centers; data were prospectively collected by each participating center throughout a web-based centralized system and then retrieved from the registry for the analysis. This prospective study enrolled 117 patients (according to Zhu criteria, 92 were affected by WAS and 25 by XLT) with appropriate hematological features and documented WAS mutation. The median follow-up was 6 years (range 1–30 years), resulting in 1110 patient years. At diagnosis, only the patients with WAS presented invasive infections, such as sepsis, meningitis, cerebral abscesses, herpetic infections, and candida infections, while patients with XLT did not present invasive infections. The most common autoimmune manifestations in patients with WAS were hemolytic anemia (20%) and vasculitis (9.3%), inflammatory bowel disease (5%), arthritis (4%), nephropathy (2%), and coeliac disease (1%). Allogeneic Hematopoietic Stem Cell Transplantation (HSCT) was performed in 71 (61%), autologous hematopoietic stem cell gene therapy (HSC-GT) in 10 (8.5%), splenectomy in 16 (14%) patients, while 26 patients (22%) received none of these therapies. The overall survival at 25-year follow-up was 75% for patients with WAS after HSCT. Considering the cut-off date year 2000, it improved to >80%. Patients with WAS treated by haploidentical HSCT with αβTCRT-/CD19 B-cell depletion or gene therapy showed 100% survival at 5 years. The overall survival rate at the 20-year follow-up of the 25 patients with XLT was 83% but with a cumulative incidence of 100% and 19% of infections and autoimmunity, respectively, at the 15-year follow-up. The evidence of the heterogeneity of WAS and XLT outcomes could be instrumental to draw updated recommendations for the management of the patients affected by these rare conditions. It would be desirable to expand the tools to estimate the risk of infectious and autoimmune events in patients with XLT and the impact of their treatment, including HSCT over time. This study was funded by the European Union–Next Generation EU–NRRP M6C2–Investment 2.1 Enhancement and strengthening of biomedical research in the NHS, Ministero della Salute (PNRR-MR1-2022-12376594). A.S., A.A., P.C., F.F., C.M.P., C.F., D.L., G.S., M.D., M.C., P.A., B.A., P.F. are part of the European Reference Network on Rare Primary Immunodeficiency, Autoinflammatory and Autoimmune Diseases (ERN-RITA, project 739543).